Modulation of behavior in zebrafish, Danio rerio, according to female reproductive status and visual and chemical cues. Issue 1 (2nd January 2019) - Cavallino, L.; Valchi, P.; Morandini, L.; Pandolfi, M.
ABSTRACT: Zebrafish, Danio rerio, is one of the most studied vertebrate models. However, there are still many aspects of its reproductive behavior to be elucidated. The aim of this work was to clarify whether males and females of this species display different behaviors according to sexual status, and the kind of cues they were exposed to (visual and/or chemical). Females in two different sexual status, pre- (PreS) or post-spawning (PostS), were exposed to single males cues (visual or chemical) or complementary cues (visual and chemical together). PreS females spent more time near the male's compartment than PostS when they were exposed to complementary cues, but no differences were found when only one cue was present. Males showed a higher proximity to females when they were exposed to visual, and both cues together, but no difference was found according to females' reproductive status. When no barrier was present, males and PreS females spent more time swimming together than males with PostS females. These results showed that females' reproductive status, and the kind of cues to which females and males are exposed to, can modulate behaviors related to reproduction. Particularly, both cues together (visual and chemical) are necessary to trigger different behaviors in females according to their reproductive status.